Traumatic Brain Injury and Inflammation: Emerging Role of Innate and Adaptive Immunity - Dardiotis, Efthimios; Karanikas, Vaios; Paterakis, Konstantinos; Fountas, Kostas; Hadjigeorgiou, Georgios M. (IntechOpen, 2012)
None